Inotropes and vasopressors: more than haemodynamics! - Bracht, Hendrik (Blackwell Publishing Ltd, 2012)
Circulatory shock is characterized by arterial hypotension requiring fluid resuscitation combined with inotropes and/or vasopressors to correct the otherwise life-threatening impairment of oxygen supply to peripheral tissues. Catecholamines represent the current therapeutic choice, but this standard is only based on empirical clinical experience. Although there is evidence that some catecholamines may be better than others, it is a matter of debate which one may be the most effective and/or the safest for the different situations. In their review in this issue of the British Journal of Pharmacology, Bangash et al. provide an overview of the pharmacology as well as the available clinical data on the therapeutic use of endogenous catecholamines, their synthetic derivatives and a range of other agents (vasopressin and its analogues, PDE inhibitors and levosimendan). The authors point out that, despite well-established receptor pharmacology, the clinical effects of these treatments are poorly understood. Hence, further investigations are essential to determine which catecholamine, or, in a broader sense, which alternative vasopressor and/or inotrope is the most appropriate for a particular clinical condition. LINKED ARTICLES: This article is a commentary on Bangash et al., pp. 2015–2033 of this issue and is commented on by De Backer and Scolletta, pp. 2012–2014 of this issue. To view Bangash et al. visit http://dx.doi.org/10.1111/j.1476-5381.2011.01588.x and to view De Backer and Scolletta visit http://dx.doi.org/10.1111/j.1476-5381.2011.01746.x